2019
DOI: 10.1111/anec.12692
|View full text |Cite
|
Sign up to set email alerts
|

Value of ST‐segment change in lead aVR in diagnosing left main disease in Non‐ST‐elevation acute coronary syndrome—A meta‐analysis

Abstract: Non-ST-elevation acute coronary syndrome (NSTE ACS) includes unstable angina pectoris and non-ST-elevation myocardial infarction. The patient with NSTE ACS has a variable severity and prognosis. Early stratification of the patient is very important in reducing the incidence of sudden death and adverse events. The electrocardiogram (ECG) is a rapid and noninvasive diagnostic method, which exerts a critical role in the assessment of early risk stratification. Left main coronary artery (LMCA) is one of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
1
16
0
7
Order By: Relevance
“…Since lead aVR reflects the myocardial perfusion of the basal septum, which is often affected by the LMCA or ostial/proximal LAD, it has gained significance in detecting acute myocardial ischemia. Due to the high mortality rates of these lesions, there has been an extensive examination of applying STE in aVR as a diagnostic and prognostic tool for these high-risk lesions [ 5 - 7 ]. The addition of diffuse ST-segment depressions in eight or more leads to the STE in aVR was found to have a predictive accuracy of 75% for LMCA or triple vessel disease [ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since lead aVR reflects the myocardial perfusion of the basal septum, which is often affected by the LMCA or ostial/proximal LAD, it has gained significance in detecting acute myocardial ischemia. Due to the high mortality rates of these lesions, there has been an extensive examination of applying STE in aVR as a diagnostic and prognostic tool for these high-risk lesions [ 5 - 7 ]. The addition of diffuse ST-segment depressions in eight or more leads to the STE in aVR was found to have a predictive accuracy of 75% for LMCA or triple vessel disease [ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of diffuse ST-segment depressions in eight or more leads to the STE in aVR was found to have a predictive accuracy of 75% for LMCA or triple vessel disease [ 5 , 8 ]. The degree of STE (>0.5 mm vs <0.5 mm) in lead aVR was associated with significantly different predictive values for left main or multi-vessel CAD in patients with the acute coronary syndrome (ACS), specifically STE > 0.5 mm in lead aVR significantly predicted high risk of having LMCA or multi-vessel CAD in a recent meta-analysis [ 7 ]. Knotts et al reported a 43% rate of coronary angiography (57 patients) as part of the evaluation for patients who presented to the ED with ECG findings of STE in lead aVR and ST-segment depressions in over seven leads [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Отведение aVR обеспечивает информацию об электрической активности базальной части межжелудочковой перегородки (МЖП). Окклюзия СтЛКА или проксимального сегмента ПНА приводит к трансмуральной ишемии базальной части МЖП с направлением вектора повреждения во фронтальной плоскости вверх, что ведет к элевации ST в aVR [6,10,21,26,31,[34][35][36]. Однако базальная часть МЖП имеет двойное кровоснабжение из первой септальной ветви ПНА и правой конусной артерии, которая часто берет начало из правой коронарной артерии (ПКА) или прямо от правого коронарного синуса.…”
Section: элевация St в отведении Avr при остром поражении стлкаunclassified
“…Следует отметить, что элевация ST в aVR может также наблюдаться при тромбоэмболии легочной артерии, диссекции аорты, критическом аортальном стенозе, миокардите, синдромах Бругада, такоцубо, отравлении трициклическими антидепрессантами, при блокаде левой ножки пучка Гиса, гипертрофии ЛЖ [6,31,32,38]. Данный ЭКГ-признак необходимо оценивать совместно с изменениями в других отведениях и клиническими данными [6,38].…”
Section: элевация St в отведении Avr при остром поражении стлкаunclassified
See 1 more Smart Citation